Unpacking the organizational culture as a sustainable distinctive competence in Knowledge Intensive Firms: the HarvestPlus case in Colombia - Grueso-Hinestroza, Merlin-Patricia; Amaya, Norbey; Peralta-Hernández, Gustavo; Pfeiffer, Wolfgang (Business: Theory and Practice, 2022)
Knowledge-Intensive Firms are a relevant research and practice field because there is much interest in factors promoting their competitiveness. Scholarly literature has noted that organizational culture is a resource is related to the achievement of competitive advantages. Nevertheless, organizational culture at Knowledge-Intensive Firms, has been scarcely analyzed regarding how it is configured and what effects it has. To explain how organizational culture at HarvestPlus, as a Knowledge-Intensive Firm, becomes a distinctive competency, a qualitative study case study design was developed. The results indicate that the predominant culture is adhocratic, it has evolved according to the different HarvestPlus phases and is a sustainable distinctive competence due to it is valuable, difficult to imitate and therefore unique. This research will be useful for scholars and practitioners of this type of organization to understand the usefulness of coordinating and integrating the organizational culture, to leadership behaviors, human resources practices and strategic alliances management, to create strategic resources, as HarvestPlus has done.